Pretty in Punk: Girls' Gender Resistance in a Boys' Subculture - Leblanc, Lauraine (Rutgers University Press, 1999)
Pretty in Punk combines autobiography, interviews, and sophisticated analysis to create the first insider's examination of the ways punk girls resist gender roles and create strong identities.Why would an articulate, intelligent, thoughtful young women shave off most of her hair, dye the remainder green, shape it into a mohawk, and glue it onto her head? What attracts girls to male-dominated youth subcultures like the punk movement? What role does the subculture play in their perceptions of themselves, and in their self-esteem? How do girls reconcile a subcultural identity that is deliberately coded “masculine” with the demands of femininity?Research has focused on the ways media and cultural messages victimize young women, but little attention has been paid to the ways they resist these messages. In Pretty in Punk, Lauraine Leblanc examines what happens when girls ignore these cultural messages, parody ideas of beauty, and refuse to play the games of teenage femininity. She explores the origins and development of the punk subculture, the processes by which girls decide to “go punk,” patterns of resistance to gender norms, and tactics girls use to deal with violence and harassment.Pretty in Punk takes readers into the lives of girls living on the margins of contemporary culture. Drawing on interviews with 40 girls and women between the ages of 14-37, Leblanc examines the lives of her subjects, illuminating their forms of rebellion and survival. Pretty in Punk lets readers hear the voices of these women as they describe the ways their constructions of femininity—from black lipstick to slamdancing—allow them to reject damaging cultural messages and build strong identities. The price they pay for resisting femininity can be steep—girls tell of parental rejection, school expulsion, institutionalization, and harassment. Leblanc illuminates punk girls' resistance to adversity, their triumphs over tough challenges, and their work to create individual identities in a masculine world.
Google-Books-ID: m8Lz1S9v4d8C
Keywords: Family & Relationships / Life Stages / Adolescence; Social Science / Popular Culture; Social Science / Women's Studies

Vanishing in Your Face: Embodiment and Representation in Lesbian Dance Performance - Kuppers, Petra (Journal of Lesbian Studies, 1998)
Lesbian dance performance has to come to terms with the cultural invisibility of the lesbian body, and the dichotomy of traditional gender representation. This paper charts strategies for the play with the invisible, the grotesque and the liminal in the dance performance of three UK-based choreographers: Emilyn Claid, Yael Flexer and Kate Lawrence. Their performances create tension between the role and the body, between the public and the private, and it is this tension that points towards alternative representational strategies.
Publisher: Routledge _eprint: https://doi.org/10.1300/J155v02n02_04

Racial Harassment, Sexual Harassment, and the Expressive Function of Law Case - Mullender, Richard (Modern Law Review, 1998)
Keywords: Sophie-Anne

A TOP NIGHT: Social Protest, Masculinity and the Culture of Drinking Violence - TOMSEN, STEPHEN (The British Journal of Criminology, 1997)
Although a wide research literature suggests a regular connection between drinking, violence and social disorder, much doubt remains as to the actual nature and significance of this link. Some strong insights into this are provided by a dual consideration of the tie between masculine social identity and heavy group drinking, and the importance of issues of male honour in the social interaction that leads to much violent behaviour. But as well as this, information from the author's detailed ethnographic study of assaults in public drinking venues illuminates the subjective experience of participation in acts of disorder and violence. This is filtered through understandings of certain forms and aspects of popular leisure as entailing social protest and resistance to middle class morality. Although masculinist and frequently destructive, this violence is interpreted by many drinkers as providing a liberating and attractive sense of release, group pleasure and carnival.

Sexual Harassment of Women Journalists - Walsh-Childers, Kim; Chance, Jean; Herzog, Kristin (Journalism & Mass Communication Quarterly, 1996)
A survey of 227 women newspaper journalists revealed that more than 60 percent believe sexual harassment is at least somewhat a problem for women journalists; more than one-third said harassment has been at least somewhat a problem for them personally. Two-thirds experience nonphysical sexual harassment at least sometimes, and about 17 percent experience physical sexual harassment at least sometimes. News sources were the most frequent harassers, and harassment ranged from degrading comments to sexual assault._
Publisher: SAGE Publications Inc
Keywords: Journalisme; Myriam; journalism

Beyond Victim or Survivor: Sexual Violence, Identity and Feminist Theory and Practice - Kelly, Liz; Burton, Sheila; Regan, Linda (Sexualizing the Social, 1996)
Keywords: Bibliographie; Nettoyer

Cultures of Consumption: Masculinities and Social Space in Late Twentieth-century Britain - Mort, Frank (Psychology Press, 1996)
Examines the construction of images of masculinity and the effect they have on identity, sexuality and sexual politics. Influences from black and white culture are explored as well as the ironies of class, colour and sexuality.
Google-Books-ID: _TiOIhE1NeEC
Keywords: Art / Popular Culture

The Sex Revolts: Gender, Rebellion, and Rock 'n' Roll - Reynolds, Simon; Press, Joy (Harvard University Press, 1996)
Iggy Pop once said of women: "However close they come I'll always pull the rug from under them. That's where my music is made." For so long, rock 'n' roll has been fueled by this fear and loathing of the feminine. The first book to look at rock rebellion through the lens of gender, The Sex Revolts captures the paradox at rock's dark heart–the music is often most thrilling when it is most misogynist and macho. And, looking at music made by female artists, it asks: must it always be this way?Provocative and passionately argued, the book walks the edgy line between a rock fan's excitement and a critic's awareness of the music's murky undercurrents. Here are the angry young men like the Stones and Sex Pistols, cutting free from home and mother; here are the warriors and crusaders, The Clash, Public Enemy, and U2 taking refuge in a brotherhood-in-arms; and here are the would-be supermen, with their man-machine fantasies and delusions of grandeur, from Led Zeppelin and Jim Morrison to Nick Cave and gangsta rap. The authors unravel the mystical, back-to-the-womb longings of the psychedelic tradition, from Pink Floyd, Jimi Hendrix, and Van Morrison to Brian Eno, My Bloody Valentine, and ambient techno. Alongside the story of male rock, The Sex Revolts traces the secret history of female rebellion in rock: the masquerade and mystique of Kate Bush, Siouxie, and Grace Jones, the demystifiers of femininity, like the Slits and Riot Grrl, tomboy rockers like L7 and P. J. Harvey, and confessional artists like Janis Joplin, Joni Mitchell, and Courtney Love.A heady blend of music criticism, cultural studies, and gender theory by two of rock's keenest observers, The Sex Revolts is set to become the key text in the women-in-rock debate.
Google-Books-ID: Acq7ZOYd_AcC
Keywords: Music / History & Criticism

Farinelli (1994)
Keywords: Bibliographie; Nettoyer

Freedom and Outrage in Art Education - Lankford, E. Louis (Journal of Aesthetic Education, 1994)
Publisher: University of Illinois Press
Keywords: Myriam

Backlash: the undeclared war against American women - Faludi, Susan (Anchor books, 1991)
Keywords: Bibliographie; Nettoyer

Settling Accounts with Subculture: A Feminist Critique - McRobbie, Angela (Feminism and Youth Culture: From ‘Jackie’ to ‘Just Seventeen’, 1991)
Although ‘youth culture’ and the ‘sociology of youth’ — and particularly critical and Marxist perspectives on them — have been central strands in the development of cultural studies over the past fifteen years, the emphasis from the earliest work of the National Deviancy Conference (NDC) onwards has remained consistently on male youth cultural forms.1 There have been studies of the relation of male youth to class and class culture, to the machinery of the State, and to the school, community and workplace. Football has been analysed as a male sport, drinking as a male form of leisure, the law and the police as patriarchal structures concerned with young male (potential) offenders. I do not know of a study that considers, never mind prioritises, youth and the family. This failure by subcultural theorists to dislodge the male connotations of ‘youth’ inevitably poses problems for those who are involved in teaching about those questions. As they cannot use the existing texts ‘straight,’ what other options do they have?
Keywords: Class Culture; Feminist Critique; Moral Panic; Sexual Double Standard; Youth Culture